Reduced T Cell and Antibody Responses to Inactivated Coronavirus Vaccine Among Individuals Above 55 Years Old - Medeiros, Giuliana X.; Sasahara, Greyce Luri; Magawa, Jhosiene Y.; Nunes, João Paulo S.; Bruno, Fernanda R.; Kuramoto, Andreia C.; Almeida, Rafael R.; Ferreira, Marcelo A.; Scagion, Guilherme P.; Candido, Érika D.; Leal, Fabyano B.; Oliveira, Danielle B. L.; et al. (Frontiers in Immunology, 2022)
CoronaVac is an inactivated SARS-CoV-2 vaccine that has been rolled out in several low and middle income countries including Brazil, where it was the mainstay of the first wave of immunization of healthcare workers and the elderly population. We aimed to assess the T cell and antibody responses of vaccinated individuals as compared to convalescent patients. We detected IgG against SARS-CoV-2 antigens, neutralizing antibodies against the original SARS-CoV-2 strain and used SARS-CoV-2 peptides to detect IFN-g and IL-2 specific T cell responses in a cohort of CoronaVac vaccinated individuals (N=101) and convalescent (N=72) individuals. Among vaccinated individuals, 95% displayed T cell or antibody responses to SARS-CoV-2 as compared to 99% convalescent individuals. However, we observed that among vaccinated individuals, males and individuals 55 years or older developed significantly lower anti-RBD, anti-NP and neutralization titers against the Wuhan strain as well as antigen-induced IL-2 production by T cells. Neutralizing antibody responses for variants Gamma and Zeta were even lower than for the Wuhan strain. Even though some studies indicated CoronaVac helped reduce mortality among elderly people, considering the current dominance of the gamma variant of concern (VOC) and potential increase of the delta VOC, in Brazil, our data support that CoronaVac vaccinated individuals above 55 years old are likely to benefit from a heterologous third dose/booster vaccine to increase immune response and likely protection.